2006
DOI: 10.1063/1.2364490
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature heat capacity of fullerite C60 doped with nitrogen

Abstract: The heat capacity Cm of polycrystalline fullerite C60 doped with nitrogen is measured in the temperature interval 2–13K. The contributions to the heat capacity from translational lattice vibrations (Debye contribution), from orientational vibrations of the C60 molecules (Einstein contribution), and from the motion of the N2 molecules in the octahedral cavities of the C60 lattice are estimated. However, no indications of the first-order phase transformation detected earlier in a dilatometric investigation of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The heat capacity of the interstitial solution (N 2 ) 0.2 C 60 was measured in the interval T = 2 -15 K using an adiabatic calorimeter [44]. It was found that the heat capacity of the solution was independent of the temperature prehistory of the sample.…”
Section: Introductionmentioning
confidence: 99%
“…The heat capacity of the interstitial solution (N 2 ) 0.2 C 60 was measured in the interval T = 2 -15 K using an adiabatic calorimeter [44]. It was found that the heat capacity of the solution was independent of the temperature prehistory of the sample.…”
Section: Introductionmentioning
confidence: 99%
“…Note that the data on the heat capacity of C 60 are essential for analyzing the heat capacities of new C 60 -containing nanomaterials, for example, elementary atomic and molecular gaseous substances that form interstitial solutions in the octahedral voids of fullerite C60 [39][40][41].…”
Section: Introductionmentioning
confidence: 99%